Calculate: 2(4-y)-3(y+3)=-11

Expression: $2\left( 4-y \right)-3\left( y+3 \right)=-11$

Distribute $2$ through the parentheses

$8-2y-3\left( y+3 \right)=-11$

Distribute $-3$ through the parentheses

$8-2y-3y-9=-11$

Calculate the difference

$-1-2y-3y=-11$

Collect like terms

$-1-5y=-11$

Move the constant to the left-hand side and change its sign

$-1-5y+11=0$

Calculate the sum

$10-5y=0$

Divide both sides of the equation by $5$

$2-y=0$

Use the commutative property to reorder the terms

$-y+2=0$

Change the signs on both sides of the equation

$y-2=0$